Automated Negotiation of Smart Contracts for Utility Exchanges between Prosumers in Eco-Industrial Parks - Krohling, Dan E. (2020)
Peer-to-Peer (P2P) Markets of prosumers trading utility surpluses (e.g., heating, cooling, or electric power) is a plausible realization of industrial symbiosis for companies in Eco-Industrial Parks (EIPs) in order to reach significant economic benefits and cut emissions. Through the synergistic co-generation and trading of utilities and industrial services, a P2P Market design makes room for socially desirable behavior despite the inherent selfish nature of each prosumer company. In this paper, a P2P Market prototype for the automated negotiation of utilities between prosumers in an EIP is proposed as a mechanism design to encourage prosumers to participate in trading surpluses. Blockchain transactions and Smart Contracts, combined with Internet of Things (IoTs) technology such as smart meters, are the implementation means to secure that the terms of exchange agreed upon will be automatically enforced. During the simulation of the EIP, each prosumer (represented by a negotiation agent) chooses whether to negotiate with another prosumer or to buy or sell its surpluses to a traditional service provider, such as a main electric power service provider or a gas provider, according to a previously learned policy while considering the context it is immersed in. Utilities between prosumers are exchanged based on a digital currency, the token, which could be readily implemented over Ethereum/Solidity platforms. Smart contract negotiations between prosumers revolve around agreeing (or not) on the price expressed in tokens of a utility profile, given the private and public information available to different parties. Simulation results highlight how automated negotiations allow prosumers to reach higher profits in the P2P Market from trading utility surpluses.